Hubungan Kecerdasan Emosi dengan Anxiety Reduction pada Mahasiswa Fakultas Farmasi Institut Kesehatan Helvetia - Manurung, Ernida Marietha; Dachi, Tilik Adil (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the relationship of emotional intelligence with anxiety reduction in students of the Faculty of Pharmacy, Institut Kesehatan Helvetia Medan 2016/2017. This study used quantitative approach. Measuring instruments used in the form of emotional intelligence scales are based on the theory of emotional intelligence by Goleman who has 30 items and anxiety reduction scales that are based on Conroy's theory have 30 items. The samples of this study were 80 students of the Faculty of Pharmacy, Institut Kesehatan Helvetia. The data analysis method used in this study is the Pearson Product Moment correlation with the correlation r = -0,649, with a significant p = 0,000 means (p <0.01). The results of the research showed that there was negative but significant correlation between emotional intelligence and student anxiety reduction. This shows that the higher emotional intelligence possessed by students, the easier it is to anxiety reduction, and the lower the emotional intelligence possessed by students, the more difficult it is to anxiety reduction.Â